Public health and corporate social responsibility: exploratory study on pharmaceutical companies in an emerging market - Tatiana Dănescu; Maria-Alexandra Popa (BMC, 2020)
Abstract Background Corporate social responsibility (CSR) is studied from many perspectives and has gained unprecedented importance in recent years, especially in emerging economies. Pharmaceutical companies play a very important role in a population's well-being and health through the CSR and corporate governance practices that they apply. Methods We used an exploratory approach to measure compliance with the Corporate Governance Code of pharmaceutical companies listed on the Romanian capital market and with practices declared through CSR. Results The results show that pharmaceutical companies are involved in actions that consider the well-being of society by offering financial support and managing various sustainable projects, targeting social and economic issues, leading public health awareness campaigns, and investing in health projects. Conclusion This study highlights the increasingly important role played by corporate governance and corporate social responsibility in pharmaceutical companies in improving public health in countries with emerging economies.